Variables relacionadas con la adopción de tecnologías de información: Caso de estudio en una empresa internacional (Variables related to the adoption of information technology: Case study in an international company) - Jaramillo, R. (Facultad de Contaduría Pública y Administración U.A.N.L., 2009)
Abstract. The study was applied in a company of international character that invests constantly in information technology. It is considered that the single fact to invest in technology is not guarantee so that this is adopted and taken advantage of optimally. The reasons were investigated that influenced in the employees, to accelerate the process of adoption of the technology. Net, that is used in the electronic payment of its suppliers. The reasons considered and applied in the study were obtained and adapted of previous studies based on the Theory of Diffusion of Innovations of Rogers, the Agencial Theory, the Theory of Action Reasoned of Fishbein and Ajzen, the Theory of the Planned Conduct of Ajzen and the Theory of the Equity of Adams. The work of field was made at the beginning of 2007, by means of a applied questionnaire to 140 employees. The results demonstrated that were not significant differences between the employees of the Shared Services of Center the company and those that do not belong to this center, with respect to the time that takes in feeling comfortable using the technology. Net. However yes differences in the reasons were identified that better explain the intention of adoption of this technology Resumen. El estudio se aplicó en una empresa de carácter internacional que invierte constantemente en tecnología de información. Se considera que el solo hecho de invertir en tecnología no es garantía para que esta sea adoptada y aprovechada óptimamente. Se investigaron las razones que influyeron en los empleados, para acelerar el proceso de adopción de la tecnología .Net, que es utilizada en el pago electrónico de sus proveedores. Las razones consideradas y aplicadas en el estudio se obtuvieron y adaptaron de estudios previos basados en la Teoría de Difusión de Innovaciones de Rogers, la Teoría Agencial, la Teoría de Acción Razonada de Fishbein y Ajzen, la Teoría de la Conducta Planeada de Ajzen y la Teoría de la Equidad de Adams. El trabajo de campo se realizó a principios de 2007, mediante un cuestionario aplicado a 140 empleados. Los resultados evidenciaron que no se encontraron diferencias significativas entre los empleados del Centro de Servicios Compartidos de la empresa y los que no pertenecen a dicho centro, respecto al tiempo que tardan en sentirse cómodos utilizando la tecnología .Net. En cambio sí se identificaron diferencias en las razones que mejor explican la intención de adopción de esta tecnología.